Three-Dimensional Generalized Dynamics of Soft-Matter Quasicrystals - Tian-You Fan; Zhi-Yi Tang (Advances in Materials Science and Engineering)
The three-dimensional generalized dynamics of soft-matter quasicrystals was investigated, in which the governing equations of the dynamics are derived for observed 12-fold symmetry quasicrystals and possibly observed 8- and 10-fold symmetry ones in soft matter. The solving methods, possible solutions for some initial- and boundary-value problems of the equations, and possible applications are discussed as well.